Improving the 3D talking head for using in an avatar of virtual meeting room - Nguyen, Anh Duc (Đại học Quốc gia Hà Nội, 2017)
Chapter 1: Introduction. Chapter 2: The 3D animated talking head. Chapter 3: OpenGL and JOGL overview. Chapter 4: Improving lip-sync ability. Chapter 5: Adding the hair and eyelashes models. Chapter 7: Conclusion.